AB0966 PROPOSAL OF OUTCOME MEASURES TO BE USED ON A 12-MONTH OPEN LABEL DRUG TRIAL IN JUVENILE SYSTEMIC SCLEROSIS. RESULTS OF THE 3RD CONSENSUS MEETING IN HAMBURG DECEMBER 2018. (June 2019) - Foeldvari, Ivan; Torok, Kathryn; Ambartsumyan, Lusine; Anton, Jordi; Beyer, Christian; Blakley, Michael; Constantin, Tamas; Reis, Patricia Costa; Curran, Megan; Cutolo, Maurizio; Galdo, Francesco Del; Denton, Christopher; et al.
Abstract : Background: Juvenile systemic sclerosis (jSSc) is an orphan disease, associated with high morbidity and mortality. New treatment strategies are much needed. To develop an open label drug trial for the treatment of jSSc patients, it is necessary to clearly define how to evaluate outcomes in this disease, which are currently not existing. A group of experts in jSSc has met annually and worked to develop an index to evaluate outcomes in this disease. Objectives: The aim of our third consensus meeting was to establish the domains and the items that should be assessed in a clinical drug trial in jSSc. Methods: In the consensus meeting 26 jSSc international experts with various specialties participated (22 voted). In a nominal group technic, moderated by DEF, was used to develop the outcome measures. Agreement was defined if 80% or more of the participants approved an item. Results: Domains and items suggested in the 2017 consensus meeting were reconsidered and selected or rejected during the 2018 meeting, as were additional domains/items (Table). Conclusion: We reached consensus on domains and items which should be assessed in an open label 1 year clinical jSSc trial. We also listed research items which should be assessed but should not currently be included as an outcome in such a trial. Disclosure of Interests: Ivan Foeldvari Consultant for: Chugai, Novartis, Kathryn Torok: None declared, Lusine Ambartsumyan: None declared, Jordi Anton Grant/research support from: Grant/research support, consultant or speakers bureau from AbbVie, Alexion, Bristol-Myers Squibb, ChemoCentryx, Gebro, GlaxoSmithKline, Novartis, Novimmune, Pfizer, Roche, Sanofi and Sobi, Consultant for: Grant/research support, consultant or speakers bureau from AbbVie, Alexion, Bristol-Myers Squibb, ChemoCentryx, Gebro, GlaxoSmithKline, Novartis, Novimmune, Pfizer, Roche, Sanofi and Sobi, Speakers bureau: Grant/research support, consultant or speakers bureau from AbbVie, Alexion, Bristol-Myers Squibb, ChemoCentryx, Gebro, GlaxoSmithKline, Novartis, Novimmune, Pfizer, Roche, Sanofi and Sobi, Christian Beyer: None declared, Michael Blakley: None declared, Tamas Constantin: None declared, Patricia Costa Reis: None declared, Megan Curran: None declared, Maurizio Cutolo: None declared, Francesco Del Galdo: None declared, Christopher Denton Grant/research support from: GlaxoSmithKline, Inventiva, CSF Behring, Consultant for: Roche-Genentech, Actelion, GlaxoSmithKline, Sanofi Aventis, Inventiva, CSL Behring, Boehringer Ingelheim, Bayer, Kim Fligelstone: None declared, Bernd Hinrichs: None declared, Antonia Höger: None declared, Francesca Ingegnoli: None declared, Ozgur Kasapcopur: None declared, Suzanne Li: None declared, Dana Nemcova: None declared, Catherine Orteu: None declared, Clarissa Pilkington: None declared, Vanessa Smith: None declared, Anne Stevens: None declared, Brandi Stevens: None declared, Allison Zheng: None declared, Dinesh Khanna Shareholder of: Eicos Sciences, Inc, Grant/research support from: Bayer, BMS, Pfizer, Horizon, Consultant for: Actelion Acceleron, Arena, Bayer, BI, BMS, CSL Behring, Corbus, Cytori, GSK, Genentech/Roche, Galapagos, Employee of: Elcos Sciences, Inc, Daniel Furst Grant/research support from: F. Hoffmann-La Roche, Genentech